Effect of Scenario Based Educational Program on Critical Care Nurses’ Knowledge, Practice and Attitude Regarding Use of Physical Restraints at a Selected Hospital in Cairo, Egypt: Lecturer - Fatma Shoeib Ali,; Fatma Abd El-Aziz Mohamed, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
There is still great controversy about the potential benefits, side effects and ethical issues associated with physical restraint (PR) use in critical care settings. Nurses’ views and attitudes toward the use of PR in controlling patients’ behavior and ensuring patient safety may create conflicts with patients’ rights, including their autonomy in making decisions for their own care.Aim of the study: To evaluate Effect of Scenario Based Educational Program on Critical Care Nurses’ Knowledge, Practice and Attitude Regarding Use of Physical Restraints at a Selected Hospital in Cairo, Egypt. Research Design: A quasi-experimental research design (pre-posttest design), was utilized in the current study.Research hypotheses: H1: The mean posttest knowledge score of nurses who are exposed to scenario based educational program of physical restraint will be higher than their pretest mean knowledge score. H2: The mean posttest practice score of nurses who are exposed to scenario based educational program of physical restraint will be higher than their pretest mean practice score.H3: Critical care nurses' attitude towards physical restraint will be positively changed after scenario based educational program.Setting: The study was conducted at selected intensive care units in Cairo, Eygept.Sample: A convenience sample of 30 critical care nurses working in the selected ICU, who were applying physical restraint to critically ill patients, were included in the current study.Tools of data collection: Four tools were used to collect data pertinent to the current study: Critical Care Nurses’ Demographic Data Sheet, Critical Care Nurses' Knowledge Regarding Use Of Physical Restraint Questionnaire, Critical Care Nurses' Attitude Regarding Use of Physical Restraint Scale. And Critical Care Nurses' Practices Regarding Use of Physical Restraint Checklist.Results: The findings of the current study showed that two third (63.3%) of the studied sample were females, less than half (46.6%) of them are in the age ranged between (25-30) years old, more than one third (43.3%) of them had diploma and technical institute nursing degree, two third (60%) of them had nursing experiences ranged from (5-10) years. Moreover, it was observed in the current study that more than third (33.3%) of the studied sample responded correctly to the following statement "Restraints should be released every 2 hours, if the patient is awake" that improved to the majority (86.6%) of them are agreed after scenario based educational program. statistical significant differences between total mean knowledge score (pre- posttest), total mean attitude score (pre-posttest), and total mean practice score (pre- posttest) before and after the program.Conclusion: The ﬁndings demonstrated that scenario based educational program could improve nurses' knowledge, attitude, and practice in relation to use physical restraint. Reducing physical restraint use leads to a more therapeutic and respectful space with a less violent milieu and greater staff effectiveness. This is in alignment with patient-centered care. The results of this study and the developed educational intervention are applicable for nurses, nursing educators, nursing managers, hospital managers, researchers and hospital policymakers.Recommendations: Development of local policies for physical restraints use including detailed descriptions of conditions requiring its use is mandatory. Physical conditions in ICU settings should be improved to provide adequate resources and personal staff. Periodic in-service training advanced care programs based on best practice guidelines for nurses working in ICU is essential to improve nurses' practice regarding use of PR. In addition, it is important to increase awareness among ICU physicians of the advantages and drawbacks, ethical implications of PR and the requirement of written physician's orders to start and remove PR since this will restrict use of PR in critical care settings.